Synthesis and Analysis of Novel Poly (2-hydroxyethyl methacrylate-acrylamid)/Clay Superabsorbent Nanocomposites (Journal of Fiber Bioengineering and Informatics, 2018)
A series of novel superabsorbent nanocomposites based on 2-hydroxyethyl methacrylate (HEMA) and acrylamid (AM) were prepared via in situ free radical polymerization, using clay (Laponite XLS) as a crosslinker and ammonium persulfate (APS) as an initiator. The structure and surface morphology of the superabsorbent nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The water absorbency was found to be 612.5 and 182.6 g H_2O^{g-1} in distilled water and 0.2% NaCl solution, respectively. In addition, the superabsorbent nanocomposites reported here might be a potentially smart material in some range of applications including adsorption materials, superabsorbent fiber and drug-delivery devices.